Origem e distribuição dos nervos axilares em fetos de bovinos azebuados - Lizardo, Frederico Balbino (2009)
In this study, the origin and distribution of the axillary nerve in 30 fetuses of zebu-crossed bovines, 20 males and 10 females, were analyzed through dissection after fixation in an aqueous solution of 10% formaldehyde. The axillary nerve was found to originate in 13.33% of the antimeres of the ventral branch of the 6th cervical (C6) spinal nerve, in 100% of the antimeres of the ventral branch of the 7th cervical (C7) spinal nerve, in 91.67% of the ventral branch of the 8th cervical (C8) spinal nerve, and in 5.00% of the ventral branch of the 1st thoracic (T1) spinal nerve. The axillary nerve extended branches to the teres minor (100,00%), deltoid (100,00%), cleidobrachial part of the brachiocephalic muscle (100,00%), subscapularis (78.33%) and teres major (11.66%) muscles. In all the animals, the aforementioned nerve issued the cranial cutaneous branch of the lower leg, which was distributed to the fascia and skin of the cranial face of the upper and lower leg. No significant differences were found in the frequency of branches of the axillary nerves issuing to the muscles of the right and left antimeres. However, statistically significant differences were found in the frequency of branches leading to the right deltoid muscle in males and females, with male fetuses showing a higher frequency of these branches.